The Applying Artificial Intelligence in Mathematics Education at SDN Larangan Dalam 01 Pamekasan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program seeks to optimize the integration of artificial intelligence (AI) in mathematics education at SDN Larangan Dalam 1, Larangan District, Pamekasan Regency, to foster 21st-century digital literacy and address the challenges posed by Industry 4.0. The community service methods employed include training, discussions, and hands-on practice in designing learning tools, developing teaching materials, and conducting AI-assisted assessments. A total of 12 teachers participated in the training, demonstrating significant skill improvement upon completion. The training evaluation revealed that 80% of the teachers were able to independently apply the training outcomes to develop AI-based learning tools. This program has the potential to serve as a sustainable model for enhancing technological skills among educators in remote areas, while boosting student motivation and innovation in mathematics learning within the Merdeka Curriculum.